Adapting the buying funnel model of consumer behavior to the design of an online health research recruitment tool. Issue 4 (14th August 2017) - Doshi, Aalap; Connally, Lisa; Spiroff, Meghan; Johnson, Anita; Mashour, George A.
Abstract : Introduction: UMHealthResearch is the University of Michigan's digital health research recruitment platform. It allows health researchers to connect efficiently with potentially eligible volunteers. Methods: In 2013, the UMHealthResearch team strategically adapted a consumer behavior model, the buying funnel, to create the Digital Health Research Participation Funnel. The Digital Health Research Participation Funnel was then used to design a more active way for potential participants to volunteer for research studies through UMHealthResearch. Results: In the 5 years before the redesign (2007–2012), an average of 1844 new accounts were created every year, whereas in the completed years after the redesign (2013–2016) the annual average improved to 3906, an increase of 111%. Conclusion: Although a randomized design was not possible in this instance, these preintervention and postintervention data suggest that the focus on user experience is an effective strategy for improving web-based research recruitment platforms.